Determination of contamination levels of Pb, Cd, Cu, Ni, and Mn caused by former lead mining gallery - Bakirdere, Sezgin; Bolucek, Cemal; Yaman, Mehmet (Springer, 2016)
In the present study, levels of metal contamination caused by former lead mining area were figured out. For this purpose, Pb, Cd, Cu, Ni, and Mn were determined not only in sediment samples taken from different places of the mining area but also in some plants taken around the mining place. In the digestion of plant samples, dry ashing procedure was applied. Flame atomic absorption spectrophotometer (FAAS) was used in the determination of analytes of interest. All the parameters in digestion and detection procedures were optimized to obtain efficient digestion and high sensitivities for analytes. Standard addition and direct calibration methods were applied to find whether there was any matrix interference to affect the determination of analytes. Mn concentration was found to be the highest for each sample analyzed. Lead concentration was found to be between 41 and 249 mg/kg in soil/sediment samples and between 2.2 and 1003 mg/kg in plant samples. The highest contamination levels for all of the analytes with the exception of Cd were found in current sediment sample.
Keywords: Mining; Contamination; Metal; FAAS